2006
DOI: 10.1162/jocn.2006.18.3.320
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Evidence for a Three-Stage Model of Deductive Reasoning

Abstract: In an event-related fMRI study, we investigated the neurocognitive processes underlying deductive reasoning. We specifically focused on three temporally separable phases: (1) the premise processing phase, (2) the integration phase, and (3) the validation phase. We found distinct patterns of cortical activity during these phases, with initial temporo-occipital activation shifting to prefrontal and then parietal cortex during the reasoning process. Our findings demonstrate that human reasoning proceeds in separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
92
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 48 publications
(21 reference statements)
13
92
2
1
Order By: Relevance
“…A recent series of results (Monti et al, 2007(Monti et al, , 2009Rodriguez-Moreno and Hirsch, 2009) nonetheless suggests that language areas are not involved in the deductive process, a finding consistent with several previous reports (Canessa et al, 2005;Fangmeier et al, 2006;Goel and Dolan, 2001;Knauff et al, 2002;Noveck et al, 2004;Parsons and Osherson, 2001;Prado and Noveck, 2007). We interpret these findings as implying that the role of language is confined to initial encoding of verbal statements into mental representations suitable for the inferential calculus.…”
Section: Deduction As a Language Based Processsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent series of results (Monti et al, 2007(Monti et al, , 2009Rodriguez-Moreno and Hirsch, 2009) nonetheless suggests that language areas are not involved in the deductive process, a finding consistent with several previous reports (Canessa et al, 2005;Fangmeier et al, 2006;Goel and Dolan, 2001;Knauff et al, 2002;Noveck et al, 2004;Parsons and Osherson, 2001;Prado and Noveck, 2007). We interpret these findings as implying that the role of language is confined to initial encoding of verbal statements into mental representations suitable for the inferential calculus.…”
Section: Deduction As a Language Based Processsupporting
confidence: 91%
“…Diverse logical domains have also been investigated. Different studies have focussed on deontic and social reasoning (Canessa et al, 2005;Fiddick et al, 2005), propositional arguments (Monti et al, 2007;Reverberi et al, 2007) along with categorical (Osherson et al, 1998;Parsons and Osherson, 2001;Rodriguez-Moreno and Hirsch, 2009) and relational syllogisms (Knauff et al, 2002(Knauff et al, , 2003Fangmeier et al, 2006). Other work has investigated the impact of familiar and unfamiliar information (Goel et al, 2000;Goel and Dolan, 2001;Noveck et al, 2004), prior beliefs (Goel and Dolan, 2003a), and emotional content (Goel and Dolan, 2003b) on the neural implementation of deductive inference.…”
Section: Introductionmentioning
confidence: 99%
“…in [37] involvement in visuospacial working memory tasks of frontal and parietal areas of the brain was postulated. As our task was spatial in nature, it was interesting to see whether it would involve both or only one (right) parietal site.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors, e.g. Fangmeier et al [37], claimed that this particular activity within the fronto-parietal network is mainly due to maintaining and processing of visuospatial information. Other studies showed frontal theta band involvement in working memory and also in other cognitively demanding tasks [39].…”
Section: Discussionmentioning
confidence: 99%
“…An array can be used to derive novel conclusions or to check given conclusions even if the relation is temporal or abstract (Boroditsky, 2000;Goodwin & Johnson-Laird, 2005). The array is a mental model of the situation, and recent evidence for the use of models in reasoning about all sorts of relations comes from studies using secondary working memory tasks (Klauer, Stegmaier, & Meiser, 1997;Vandierendonck & De Vooght, 1997) and neuroimaging (e.g., Fangmeier, Knauff, Ruff, & Sloutsky, 2006;Knauff, Fangmeier, Ruff, & Johnson-Laird, 2003).…”
mentioning
confidence: 99%